Investigación y desarrollo de un prototipo de Sistema Experto para Scheduling en Pymes con entorno Job Shop - Álvarez Pomar, Lindsay; Caicedo Cárdenas, Camilo; Malaver Gallego, Mario; Méndez Giraldo, Germán (Revista Científica, 2011)
In the current competitive environment, where both sudden changes in products demand and economic globalization demand every area of the organization to keep a good performance, the effective scheduling has become not only a challenge, but also a necessity to survive within the marketplace. Due to the fact that most of Colombian enterprises are SMEs and most of them have their productive systems set up as job shop, it becomes important to pay special attention to job shop scheduling. Job shop scheduling problem complexity, in addition to low availability of specialized staff to perform this task, make necessary to resort to the use of computational tools, somehow innovative, which facilitate the scheduling function. In order to tackle this problem, through this research has been created a knowledge base and has been designed a methodology for its implementation into an expert system for job shop scheduling, which is applicable to the SMEs.